Novel bi- and trinuclear gallium halides and hydrides with acyclic and bicyclic guanidinate substituents: synthesis and reactivity - Rudolf, Daniel Thomas; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2010)
We report on the synthesis and characterization of new molecular Ga halides and hydrides with acyclic guanidinate substituents with bicyclic guanidinate substituents. Acyclic guanidinates were found to adopt terminal bonding modes like in the dimeric GaII compound [(iPr2N)C(NiPr)2GaI]2. In contrast, bicyclic guanidinates prefer bridging bonding modes. Hence, the reaction between Me3N·GaH3 and htbo (1,4,6-triazabicyclo[3.3.0]oct-4-ene) affords the binuclear GaIII hydride [H2Ga(μ-tbo)]2. This new hydride turned out to be unstable in solution at 25 °C, dihydrogen is slowly eliminated. In the solid state, however, the hydride is stable up to 80 °C. The thermodynamic properties of this and similar dehydrogenation reactions were studied my means of quantum chemical calculations. With Ga2H5(μ3-O)(μ-tbn)2 and Ga2H5(μ3-O)(μ-hpp)2, two new hydrides were synthesized which can be regarded as the first hydrolysis intermediates of binuclear Ga hydrides with bridging guanidinate substituents.
Gesehen am 22.06.2023